The role of intergenerational educational mobility and household wealth in adult obesity: Evidence from Wave 2 of the World Health Organization's Study on global AGEing and adult health - Stella T. Lartey; Costan G. Magnussen; Lei Si; Barbara de Graaff; Richard Berko Biritwum; George Mensah; Alfred Yawson; Nadia Minicuci; Paul Kowal; Godfred O. Boateng; Andrew J. Palmer (PUBLIC LIBRARY SCIENCE, 2022)
BackgroundObesity has emerged as a major risk factor for non-communicable diseases in low and middle-income countries but may not follow typical socioeconomic status (SES)-related gradients seen in higher income countries. This study examines the associations between current and lifetime markers of SES and BMI categories (underweight, normal weight, overweight, obese) and central adiposity in Ghanaian adults.MethodsData from 4,464 adults (2,610 women) who participated in the World Health Organization's Study on global AGEing and adult health (SAGE) Wave 2 were examined. Multilevel multinomial and binomial logistic regression models were used to examine associations. SES markers included parental education, individual education, intergenerational educational mobility and household wealth. Intergenerational educational mobility was classified: stable-low (low parental and low individual education), stable-high (high parental and high individual education), upwardly (low parental and high individual education), or downwardly mobile (high parental and low individual education).ResultsThe prevalence of obesity (12.9%) exceeded the prevalence of underweight (7.2%) in the population. High parental and individual education were significantly associated with higher odds of obesity and central adiposity in women. Compared to the stable low pattern, stable high (obesity: OR = 3.15; 95% CI: 1.96, 5.05; central adiposity: OR = 1.75; 95% CI: 1.03, 2.98) and upwardly (obesity: OR = 1.71; 95% CI: 11.13, 2.60; central adiposity: OR = 1.60; 95% CI: 1.08, 2.37) mobile education patterns were associated with higher odds of obesity and central adiposity in women, while stable high pattern was associated with higher odds of overweight (OR = 1.88; 95% CI: 1.11, 3.19) in men. Additionally, high compared to the lowest household wealth was associated with high odds of obesity and central adiposity in both sexes.ConclusionStable high and upwardly mobile education patterns are associated with higher odds of obesity and central adiposity in women while the stable high pattern was associated with higher odds of overweight in men.